Risk Management Maturity Model for Public Higher Education Institution - Suesat, Siriluk; Koolnapadol, Taweesil; Yongsorn, Chatupol (Rajapark Journal, 2022)
This quantitative research is aimed to analyze contents of the risk management process and construct risk management maturity model in Public Higher Education Institutes of the Office of the Higher Education Commission (OHEC). There were 385 sample sizes, which consisted of the administrators and the academic instructors. The multi-stage sampling was used to select 30 public higher institutes. The data were collected by using questionnaire. Data were analyzed by exploratory factor analysis. The results showed that the 75 variables can be divided into five groups with an Eigen value >1.00, which explained the variance of 75 variables for 66.81%. The maturity of risk management was divided into five levels, as follows: (1) natured; (2) established; (3) organized; (4) managed; and (5) integrated.